MODELLING OF FORMATION OF NOISE OF THE EQUIPMENT FOR PROCESSING OF LENGTHY DETAILS IN PROPORTIONAL PREMISES - S.A. SHAMSHURA; О.А. KALASHNIKOVА (Advanced Engineering Research)
In article results of the theoretical description шумообразования the large-sized equipment in a proportional premise are resulted at presence шуморзащитной designs. Proceeding from conditions of maintenance of a sanitary code of noise expression of a necessary thickness of elements of a soundproofing design is received. Dependences of capacity with reference to lengthy details are received.